Analysis of the application of brain-computer interfaces of a selected paradigm in everyday life - Mróz, Katarzyna; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2022)
The main objective of this paper is to carry out a research on the analysis of the use of brain-computer interface in everyday life. In this paper, various methods of recording brain activity are presented. Special attention is given to electroencephalography, which was used in the study. The brain activity used in the brain-computer interface and the general principle of brain-computer interface design are also described. The performed study allowed to develop an analysis of the obtained results in the matter of evaluating the usability of brain-computer interfaces using motor imagery. In the final stage, it was possible to evaluate the usability of the brain-computer interface in everyday life.